Mucopolysachharidosis-II: A Rare Case Report - Baxi, Kalgi; Jagati, Ashish; Agarwal, Pooja (Nepal Journal of Dermatology, Venereology & Leprology, 2020)
Mucopolysaccharidosis belongs to a group of metabolic disorders caused by absence or defective activity of lysosomal enzymes. Mucopolysaccharides are major components of intercellular connective tissue and defect in their metabolism leads to an accumulation of incompletely degraded mucopolysaccharides in the lysosomes which affect various body systems through enzymatic activity. We present a case of mucopolysaccharidosis type II with hallmark cutaneous features, mild mental retardation associated with radiological changes.